Taraftar bakış açısıyla futbol kulüplerinin ilişkisel pazarlama faaliyetlerinin değerlendirilmesi - Göksu, Tekmil Sezen (My University, 2017)
ÖZETTaraftar Bakış Açısıyla Futbol Kulüplerinin İlişkisel Pazarlama Faaliyetlerinin DeğerlendirilmesiAmaçModern pazarlama faaliyetlerinin içinde oluşan ilişkisel pazarlamanın, profesyonel futbol kulüplerinde uygulanmasının, taraftardan elde edilen verilerle değerlendirilmesi, demografik özelliklerine göre arasındaki farkın incelenmesidir. Gereç ve YöntemÇalışmaya 766 taraftar gönüllü olarak katılmıştır. Taraftarlara, kişisel bilgi formu ve ilişkisel pazarlama hizmet ölçeği, internet üzerinden e-anket yoluyla uygulanmıştır. Araştırmada elde edilen veriler SPSS 20.0 (Statistical Package for Social Sciences) kullanılarak analiz edilmiştir. Verilerin normal dağılım gösterip göstermediği Kolmogrov-Smirnof testi ile analiz edilmiş ve normal dağılım göstermediği anlaşılmıştır. (p<0,05). Bunun sonuncunda; Mann Whitney U ve Kruskal Wallis H testleri uygulanmıştır.Bulgular ve Sonuçlar Sonuç olarak örneklem grubunun cinsiyet, yaş, medeni durum, eğitim ve destekledikleri takımlara göre ilişkisel pazarlama hizmetlerini değerlendirme düzeyleri arasında anlamlı farklılık tespit edilirken, aylık gelir ve passolig kullanma düzeyleri arasında anlamlı farklılık tespit edilmemiştir. ABSTRACTEvaluation of relational marketing activities of football clubs from a fan perspectivePurposeRelational marketing that occurs in modern marketing activities, the implementation of professional football clubs, assessing the data obtained from the fans, is to examine the differences between demographic characteristics.Materials and Methods766 followers voluntarily participated in the study. Personal information form and ‘’Relational Marketing Service Scale’’ were applied to the fans by e-survey via internet. The obtained data were analyzed using SPSS 20.0 program in the study.Finding and ResultsThe results of this study the sample group of the gender variable in the dimension in customer relations and satisfaction, customer relations and satisfaction variable in the age range 18-25, communication, orientation and confidence of the fans, the size of the variable marital status of the fans in being the bachelor customer relations and satisfaction, communication, and orientation of fans with confidence in the dimension, the size of the education variable and satisfaction, customer relations, communication, orientation and confidence of the fans, the size of and Support Team, according to the supporters of Besiktas gymnastics club's customer relations and relational marketing services detected significant differences between levels of satisfaction in the dimension of evaluation, the levels of significant differences between monthly income and have not been identified using passolig.
Keywords: Customer Relations Management; Ekonomik yönleri; Football Clup; Fun; Futbol kulüpleri; İlişkisel Pazarlama; Müşteri ilişkileri Yönetimi; Pazarlama; Relationship Marketing; Spor; Spor Endüstirsi; Sport Industry; Taraftarlık